2000
DOI: 10.1002/1097-0088(200009)20:11<1285::aid-joc536>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

ENSO and climatic signals across the Indian Ocean Basin in the global context: part I, interannual composite patterns

Abstract: This study focuses on the interplay between mean sea level pressure (MSLP), sea surface temperature (SST), and wind and cloudiness anomalies over the Indian Ocean in seasonal composite sequences prior to, during, and after strong, near-global El Niñ o and La Niñ a episodes. It then examines MSLP and SST anomalies in the 2-2.5-year quasi-biennial (QB) and 2.5-7-year low-frequency (LF) bands that carry the bulk of the raw ENSO signal. Finally, these fields were examined in conjunction with patterns of correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
175
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(197 citation statements)
references
References 84 publications
(33 reference statements)
19
175
0
Order By: Relevance
“…Nevertheless, we suspect that, apart from global climatic phenomena -such as the North Atlantic Oscillation (NAO) and the El Niño-Southern Oscillations (ENSO) -as main explanatory variables (e.g. Reason et al ., 2000;Rodrigo et al ., 2001;Haylock & Goodess, 2004), the influence of topography may account for differences among regions. Deacon et al .…”
Section: Rainfall Regimes Comparedmentioning
confidence: 99%
“…Nevertheless, we suspect that, apart from global climatic phenomena -such as the North Atlantic Oscillation (NAO) and the El Niño-Southern Oscillations (ENSO) -as main explanatory variables (e.g. Reason et al ., 2000;Rodrigo et al ., 2001;Haylock & Goodess, 2004), the influence of topography may account for differences among regions. Deacon et al .…”
Section: Rainfall Regimes Comparedmentioning
confidence: 99%
“…However, it is not clear whether ENSO, IOD, TBO, and SIOD are completely independent of each other, as extensively discussed in several papers [e.g., Reason et al, 2000;Xie et al, 2002;Meehl and Arblaster, 2002;Ashok et al, 2003;Shinoda et al, 2004;Bracco et al, 2005;Schott et al, 2009;Morioka et al, 2013]. For example, the TBO is defined as the tendency for a relatively strong monsoon year to be followed by a weak one, and vice versa [Meehl and Arblaster, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term IOB SST warming has commonly been attributed to the anthropogenic effect associated with global warming [Barnett et al, 2005;Pierce et al, 2006]. Nevertheless, decadal changes over the Indian Ocean have been found closely related to ENSO [Cole et al, 2000;Allan et al, 1995;Reason et al, 2000;Xie et al, 2010;Chowdary et al, 2012]. For example, Allan et al [1995] suggested that the epochal changes in the mean condition over the south Indian Ocean are in-phase with ENSO-related correlation patterns.…”
Section: Introductionmentioning
confidence: 99%